Efficiency of Students’ Needs Assessment Application Facilitated by Text Communication Media - Hanggara, Guruh Sukma; Setyaputri, Nora Yuniar; Ariyanto, Restu Dwi (Jurnal Kajian Bimbingan dan Konseling, 2019)
Needs assessment is the main thing performed by school counselors as a basis for developing a guidance and counseling service program. In conducting needs assessment, problems that frequently occur are related to ratios, feasibility and practicality of instruments, as well as needs assessment procedures. One solution that can be used to overcome these problems is the use of application analysis needs of students based on text communication media. This research aims to determine the efficiency of students’ needs analysis application based on text communication media on vocational high school students. The research method used was experiment with the one-group pretest-posttest design technique. The research population was 45 vocational high school counselors in Kediri city. The percentage of random sampling was 25% of the total population, so the number of subjects was 11 people. The research instrument was the Students’ Needs Efficiency Assessment Questionnaire by the school counselor and interviews. The research data were analyzed in descriptively and comparative tests. Based on the analysis results, the needs assessment of text-based media communication is to improve the efficiency of students’ assessment declared efficient.